The Concept of ааһ ‘piala’ in the Linguoculture of the Kalmyks - Esenova, Galina B.; Esenova, Tamara S. (The New Research of Tuva, 2025)
The present article analyzes “ааһ” ‘piala’ (“bowl”/“cup”) as a concept of Kalmyk linguoculture. The theoretical and methodological basis of the study comprises the principles of Russian linguistic conceptology. The source material consisted of language data extracted through continuous sampling from existing lexicographic sources on the Kalmyk language, dictionaries of related languages, as well as essay materials recorded from Kalmyk respondents in July 2025 in Elista (Kalmykia).It is established that in the Kalmyk language, the concept of “ааһ” ‘piala’ exhibits variability of expression, characterizing “ааһ” in terms of a) material, b) form, c) size, d) function. In contemporary Kalmyk speech, the most frequently used denotations are the lexemes “ааh” and “shaazn”, with the name of the concept itself being “ааh”. The core of the concept is the lexeme “ааh”; systemic synonyms include “tsӧgts”, “shaazn”; the periphery consists of “badr”, “mandl”, “savl”, “tagsh”, “tsoma”, and “tsar”.The conceptual content of “ааh” includes: a cup intended for tea, for offering on an altar, made of wood, porcelain, or faience. The perceptive and figurative aspect of the concept is a whole, clean cup filled to the brim with tea, associated with happiness. The value component is inextricably linked to the contents of “ааh” — “tsä” ‘tea,’ which is classified as “tsakhan idän” ‘white, auspicious food’, and this underscores the importance of the concept in Kalmyk culture. This explains the use of «ааһ» in the daily life of the Kalmyks, in significant rituals, customs, behavioral codes, and texts. Among contemporary Kalmyks, “modn ааһ”, “mӧngn ааh”, “agch ааh” are associated with the nomadic past of the people, with male herders and warriors; “tsӧgts ааһ” — with the spiritual sphere.The concept of “ааh” ‘piala’ reflects features of the nomadic life of the Kalmyks, their natural environment, beliefs, interactions with other peoples, and mindset. The concept has undergone a prolonged process of “enlanguaging” and conceptualization in linguoculture, while retaining its status as a deeply ethnic, culturally significant symbol.
Keywords: Kalmyks; Kalmyk language; Kalmyk culture; material culture; concept of culture; ааһ; piala; component of a concept